Optimum measurement condition for V(x) method using the line-focus-beam ultrasonic-material-characterization system. (15th June 2021) - Ohashi, Yuji; Yokota, Yuui; Yamaji, Akihiro; Yoshino, Masao; Kurosawa, Shunsuke; Kamada, Kei; Sato, Hiroki; Toyoda, Satoshi; Hanada, Takashi; Yoshikawa, Akira
Abstract: Optimum measurement condition of the V ( x ) method proposed as a fast scanning technique of the line-focus-beam ultrasonic material characterization system was theoretically investigated to realize more accurate measurement. Through numerical calculation, it was clarified that the appropriate defocus position z m with higher sensitivity used in the V ( x ) measurement depended on the waveform attenuation of V ( z ) curves. It was also clarified that the measurement error caused by the focal distance change due to temperature change in the water coupler could be reduced by choosing the lower defocus position as z m . A method for measuring the surface profile of the specimen by applying the V ( x ) method with z m > 0 was proposed in order to correct measurement error due to warpage of specimen surface.